Benchmarking the implementation of recommended food environment policies in Norway using the Healthy Food Environment Policy Index (Food-EPI). (30th September 2020) - Torheim, L E; Løvhaug, A L; Henjum, S; Terragni, L; Roos, G
Abstract: Background: Obesity prevalence in Norway has increased over the past decades despite political objectives and strategies for obesity prevention. Healthy food environments have the potential to improve the diet of the population and decrease the burden of disease. Governments play a critical role to form such environments. The aim of the study was to assess the efforts of the Norwegian Government towards creating healthier food environments and suggest actions using the Healthy Food Environment Policy Index (Food-EPI) methodology. Methods: Evidence of policy implementation was assembled and verified by government stakeholders for 45 good practice indicators across 12 policy and infrastructure support domains. Independent public health nutrition experts from academia and civil society (n = 34) assessed the level of implementation of each indicator compared with international best practices, using an online tool. Results: Most indicators were rated at "medium" level of implementation (51%). An almost equal number of indicators were rated at "high" and "low" level of implementation (21% and 28%, respectively). None of the indicators were rated as "very low, if any" level of implementation. More indicators under the infrastructure domain were rated at "high" or "medium" as compared with the policy domain. The expert panel developed a list of priority actions that should be implemented to improve the food environment, including actions regarded as most effective in decreasing social inequalities in diet. The top priority action was that the Government should to a larger extent use price and taxes to change food consumption. Conclusions: The Food-EPI framework and process can be used to identify gaps in national policy implementation and to develop recommendations for strengthened policy action supported by a coalition of public health experts.